Concurrent amoebic and histoplasma colitis: a rare cause of massive lower gastrointestinal bleeding. - Koh, P.; Roslani, A.; Vimal, K.; Shariman, M.; Umasangar, R.; Lewellyn, R. (2010)
Infective colitis can be a cause of massive lower gastrointestinal bleeding requiring acute surgical intervention. Causative organisms include entamoeba and histoplasma species. However, concurrent colonic infection with both these organisms is very rare, and the in vivo consequences are not known. A 58-year-old male presented initially to the physicians with pyrexia of unknown origin and bloody diarrhea. Amoebic colitis was diagnosed based on biopsies, and he was treated with metronidazole. Five days later, the patient developed massive lower gastrointestinal bleeding with hemorrhagic shock. Emergency total colectomy with end-ileostomy was performed. However, he deteriorated and died on the second postoperative day. Histopathological examination revealed multiple deep ulcers at the hepatic flexure where fungal bodies of mycelial and yeast forms were noted. Isolated lymph nodes showed abscess formation with fungal bodies. Infective fungal colitis with Histoplasma capsilatum was diagnosed. In vitro, amoebic parasites can increase virulence and pathogenicity of histoplasma which may account for the fulminant presentation in this patient. Although rare, this unusual dual infection should be considered in the differential diagnosis of infective colitis, as appropriate antimicrobial treatment may prevent progression to massive lower gastrointestinal bleeding, obviating the need for urgent surgical intervention.